Separation of lysozyme using ultrafiltration membrane, effect of ph and ionic strength on flux and rejection - Nur Sharlinawati, Md. Said (2008)
The separation of solid, macro molecule and non-dissolve particle results from the fermentation process which contains the desired product is a first step to get the product for the industry. One of the methods to separate this non-dissolve is by using ultrafiltration membrane. The main objective of this research is to investigate the effect of pH and ionic strength on membrane flux and rejection as well as to determine the optimum pH and ionic strength in order to obtain high flux and high lysozyme rejection by using ultrafiltration membrane. The range of pH that has been used is between 5 until 8. From the result, the alkaline conditions of the lysozyme solution resulted maximum membrane flux and rejection. This was due to the absorption of lysozyme onto the membrane and the charges between the membrane and the lysozyme solution itself. The optimum pH for high membrane flux and rejection and rejection is pH 8 while the optimum ionic strength for membrane flux is 0.5 M NaCl.